Efficacy of Nonpreserved Sodium Hyaluronate Artificial Tears in Dry Eye Disease Patients Treated with Prostaglandin Analogs for Primary Open-Angle Glaucoma: A Prospective, Nonrandomized, Open-Label Pilot Study - Giulia Coco; Danilo Iannetta; Igino Febbraro; Ester Elmo; Gianluca Manni (Journal of Ophthalmology)
Purpose. Dry eye disease (DED) can be triggered using preserved ophthalmic formulations or prostaglandin analogs. In this prospective, nonrandomized, open-label pilot study, we evaluated the efficacy of a 0.15% hyaluronic acid (HA) nonpreserved ophthalmic formulation in decreasing DED symptoms in patients with open-angle glaucoma treated with prostaglandin analogs. Methods. 30 patients with DED receiving chronic treatment with prostaglandin analogs for primary open-angle glaucoma or ocular hypertension were administered ophthalmic formulations 3 times daily for 12 weeks. Foreign body sensation, burning, stinging, dryness, pain, frequency of symptoms, Ocular Surface Disease Index (OSDI), conjunctival hyperaemia, corneal fluorescein staining (CFS), tear film break-up time (TBUT), best-corrected visual acuity, Schirmer test results, and 25-item National Eye Institute Visual Function Questionnaire score between the baseline and 4 and 12 weeks were evaluated. Results. The analysis shows that all primary endpoints improved; in particular, burning sensation and the frequency of symptoms after 4 and 12 weeks of treatment (p<0.001) and dryness and pain after 12 weeks of treatment (p<0.001 and p=0.03, respectively) were reduced significantly. Secondary outcomes confirmed the positive results, with a statistically significant change in the OSDI score and CFS between the baseline and 4 (p=0.02 and p<0.001, respectively) or 12 weeks (both p<0.001) and TBUT after 4 weeks (p=0.01). Conjunctival hyperaemia improved in both eyes in >90% of cases at 12 weeks of treatment. Conclusion. The present study shows that the ophthalmic formulation containing 0.15% HA has a promising beneficial effect on reducing the signs and symptoms of DED in patients treated with prostaglandin analogs.